Tender Offers, Transactions Costs and the Theory of the Firm - Smiley, Robert (The Review of Economics and Statistics, 1976)
W HILE economists generally recognize that takeover bids limit managers' opportunity sets, empirical evidence on the efficacy of this constraint has heretofore been lacking. This paper develops a state preference model of a tender offer and the risk adjusted transactions costs of the offer are shown to be the constraining mechanism. We then show that, under certain conditions, observation of rates of return and measures of risk can lead to the estimation of the size of transactions costs. These costs are estimated using a sample of 95 tender offers that occurred in the United States between 1956 and 1970. The objective of each of the offers was a transfer of control of the target firm.